Afterword: some reflections on implicit religion and ordinary theology - Astley, Jeff (Mental health, religion & culture, 2013)
This brief piece relates Edward Bailey's concept of implicit religion, together with some themes from the papers published in this special issue, to Astley's concept of ordinary theology. In particular, it attends to their different, but overlapping, focal concerns and their shared emphasis on a spiritual core of personal meaningfulness.